Hervorming van die Suid-Afrikaanse huweliksgoederereg* II - Vorster, I. (Koers, 1977)
“Seen in the global context, the South African Law of husband and wife has, for better or worse, fallen behind developments overseas. Legal equality of husband and wife is by now firmly enshrined in the laws of Germany, France, the Netherlands, the United States of America and other Western countries”1).